PERANAN PEREMPUAN DALAM PERBANKAN SYARIAH (Suatu Analisis Ekonomi Mikro) - Rahim, Abdul; Rahim, Abdul (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2015)
The role of women in society in reproduction aspect, economic, social, politic, and Islamic leadership placed women as members in community activities or organizations. This is proved by the fact that women who are actively in organizations aren?t brave enough like men. This is become a reason why the proposed program of women is not so much to be accepted and implemented into the existing political world. The factors influence women's involvement in their role in society is education as a crucial factor because all the tasks entrusted to women can be done because of their education. This means that there is positive correlation between tasks and education.